Effects of Straw Management and Nitrogen Application Rate on Soil’s Physicochemical Properties and Rice Yield in Saline–Sodic Paddy Fields - Cheng Ran; Jiaquan Li; Ya Gao; Yaoru Xie; Yangyang Li; Jiguo Yang; Yanqiu Geng; Liying Guo; Dapeng Gao; Xiwen Shao (Plants)
Straw return plays a vital role in crop yield and sustainable agriculture. Extensive research has focused on the potential to enhance soil fertility and crop yield through straw return. However, the potential impacts of straw return on saline–sodic soils have been relatively neglected due to the unfavorable characteristics of saline–sodic soils, such as high salinity, poor structure, and low nutrient contents, which are not conducive to crop growth. Therefore, a two-year field experiment was conducted to assess the effects of straw management (retention or removal) with nitrogen fertilizers (0, 90, 180, 270, and 360 kg N ha−1) on soil aggregates, soil chemical properties, and rice yields in saline–sodic soil. The results showed that straw return with nitrogen fertilization significantly decreased the soil exchange sodium percentage (ESP) and the percentage and organic carbon contribution of silty clay particles and also significantly increased the soil aggregate stability, organic matter (SOM), and percentage and organic carbon contribution of macroaggregates. However, there was no significant difference between 270 kg N ha−1 and 360 kg N ha−1 for all soil indicators under straw return. Straw return significantly increased rice grain yield by 5.77% (two-year average) compared to straw removal. The highest grain yield of 8.01 t ha−1 (two-year average) was obtained from straw return combined with 270 kg N ha−1. However, since this experiment was conducted for only two years, the positive effects of long-term straw return on soil and rice yield could have been greater. Therefore, the application of 270 kg N ha−1 in the early stages of straw return is a promising management practice for improving saline–sodic soils and increasing rice yields.